2009
DOI: 10.1530/eje-08-0699
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the fasting free fatty acid concentration into quantitative insulin sensitivity check index improves its association with insulin sensitivity in adults, but not in children

Abstract: Objective: Based on fasting insulin and glucose, several indices of insulin sensitivity have been developed in adults. Recently, it has been demonstrated that incorporation of the fasting free fatty acid (FFA) concentration improves the association with insulin sensitivity in adults. We investigated the association of clamp-derived insulin sensitivity with indices of insulin sensitivity derived from fasting blood in prepubertal children and adults, with and without incorporation of FFAs. Design and methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The HEC technique is the gold standard and frequently sampled intravenous glucose tolerance (FSIVGTT) the silver standard in estimating IR However, because they are costly, time‐consuming, invasive, and unphysiological methods, HEC and FSIVGTT are not appropriate in epidemiological studies. Some simple indexes of IR, such as HOMA‐IR and the quantitative insulin sensitivity check index, do not need the intravenous administration of exogenous insulin or glucose and are the most commonly used tools in clinical and epidemiological studies . However, the calculation of these simple indexes requires an insulin assay, which is likely to cause significant bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEC technique is the gold standard and frequently sampled intravenous glucose tolerance (FSIVGTT) the silver standard in estimating IR However, because they are costly, time‐consuming, invasive, and unphysiological methods, HEC and FSIVGTT are not appropriate in epidemiological studies. Some simple indexes of IR, such as HOMA‐IR and the quantitative insulin sensitivity check index, do not need the intravenous administration of exogenous insulin or glucose and are the most commonly used tools in clinical and epidemiological studies . However, the calculation of these simple indexes requires an insulin assay, which is likely to cause significant bias.…”
Section: Discussionmentioning
confidence: 99%
“…20 The HEC technique is the gold standard and frequently sampled intravenous glucose tolerance (FSIVGTT) the silver standard in estimating IR 21 ical studies. 22,23 However, the calculation of these simple indexes requires an insulin assay, which is likely to cause significant bias.…”
Section: Ir-compensatory Hyperinsulinemia Induces Carotid Body Overacmentioning
confidence: 99%
“…In contrast to adults, fasting FFAs in prepubertal children were not associated with IR as measured by the euglycemic-hyperinsulinemic clamp (24). Although an inverse relation between FFAs and fasting insulin has been reported in prepubertal children, other studies showed no relation of FFAs with fasting insulin in both prepubertal and pubertal children (2428). Lipid infusion, which results in elevated FFA levels, increased IR in pubertal but not in prepubertal children (29).…”
Section: Discussionmentioning
confidence: 99%
“…RQUICKI was calculated as 1/(log fasting insulin (mU/mL) 1 log fasting glucose (mg/dL) 1 log fasting NEFA (mmol/L)). 20 Incremental AUCs (iAUCs) were calculated by the conventional trapezoid rule after the subtraction of baseline reading. Insulin response corrected for glucose was defined as iAUC insulin/glucose (0-120 min) .…”
Section: Calculationsmentioning
confidence: 99%